Answer:
Y=2x+5
Step-by-step explanation:
Move the variable (x) to the right
2y= 10-4x
divide both sides of the equation by 2
y=5-2x
and then reorder the terms
y=-2x+5
:)
Answer:
y=-2x+5
Step-by-step explanation:
hope i helped
The length of the other leg of a right angle triangle is, 10.95 units
A triangle is a three sided polygon, which has three vertices and three angles which has the sum 180 degrees.
Given that;
A right angle triangle has a hypotenuse of length 13 units and a leg of length 7 units.
Now, By the Pythagoras theorem, we get;
⇒ Hypotenuse² = Perpendicular² + Base²
⇒ 13² = 7² + Base²
⇒ 169 = 49 + Base²
⇒ Base² = 169 - 49
⇒ Base² = 120
⇒ Base = √120
⇒ Base = 10.95 units
Learn more about the triangle visit;
#SPJ2
Answer: y = -x + 5 and y = -x - 7 (see attached graph)
Step-by-step explanation:
y =
= 9(x + 1)⁻¹
Use the product rule to find the derivative
a = 9 a' = 0
b = (x + 1)⁻¹ b' = -(x + 1)⁻²
ab' + a'b
= 9[-(x + 1)⁻²] + 0[(x + 1)⁻¹ ]
=
Set the derivative equal to the desired slope of -1 to solve for x
-1 =
-(x + 1)² = -9
(x + 1)² = 9
√(x + 1)² = √9
x + 1 = +/- 3
x + 1 = 3 x + 1 = -3
x = 2 x = -4
Plug those values into the original equation to solve for y:
y =
=
= 3
(2, 3)
y =
=
= -3
(-4, -3)
Next, plug in the given slope (-1) and the coordinates above into the Point-Slope formula y - y₁ = m(x - x₁) to find the equations:
m = -1, (x₁ y₁) = (2, 3) m = -1, (x₁ y₁) = (-4, -3)
y - 3 = -1(x - 2) y + 3 = -1(x + 4)
y - 3 = -x + 2 y + 3 = -x - 4
y = -x + 5 y = -x - 7
Answer:
First tangent line:
Second tangent line:
Notice: slope of -1 means that both are equal to -1, so
Solution steps:
- Add 1 to both sides
- Divide both sides by 3
- Multiply both sides by 3
- Subtract 1 from both sides
- Square both sides
- Take the square root of both sides
PLSS HELP!!
Answer:
Below;)
Step-by-step explanation:
We know force = mass * acceleration
So Given, mass = 0.6 mg
Hence, Mass: 0.6 mg = 10^-6 * 0.6 kg
Also Acceleration = 7.5 km/s²
We know 1km = 1000 m
Putting values, we get Force as:
Answer:
Option (D)
Step-by-step explanation:
Standard equation of a quadratic function is,
ax² + bx + c
Comparing this function with the given quadratic function,
f(x) = 2x² - 4x - 3
a = 2, b = -4 and c = -3
By using quadratic formula to get the value of x,
x =
=
=
=
=
Therefore, Susie made a mistake in step IV.
Option (D) is the answer.
simplify this